Recruitment sources for supervisors in the manufacturing sector in Malaysia - Mustafa, Munauwar; Ghazali, Zahiruddin; Kassim, Mohd Shah; Hasan, Hasnizam (2000)
This study was carried out to describe the current recruitment for supervisors according to the ownership types, and sizes in the manufacturing sector. The population for this research consisted of all companies (with a minimum of 75 employees) in the manufacturing sector in Malaysia.The population frame was the listing of 3214 companies in the 1998 directory provided by MIDA (Malaysian Industrial Development Agency) Samples were chosen by using the stratified random sampling according to the industries.Data were collected by means of mail questionnaire.1907 questionnaires were mailed to the selected companies.Minus the undelivered mails, 130 questionnaires were received representing 8.27 percent response rate.Job posting on bulletin board or printed bulletins leads the most frequently used recruitment methods for supervisors, followed by newspaper advertising, skill inventories, and employee referrals.This finding emphasizes the importance of current employees as a source to fill up vacancies at the supervisory level since other than newspaper advertising all sources are from the internal recruitment.No significant difference in terms of sizes and types of ownership was found among these most frequently used methods.However, this study also finds that manufacturing companies in Malaysia do use other sources to recruit supervisors even though collectively the usage percentages are low.These sources include internship or practical training,publicly funded employment agencies, private employment agencies, former employees, walk-ins or unsolicited applications, customers, campus visit, suppliers and also trade unions.Another important finding of this study is that only 25.6 percent of the organizations do maintain a record on time-lapse data i.e. the average time that elapses between points of decision making for each recruitment source used and only 24.2 percent of the organizations do maintain a record on yield ratio i.e. the ratio of applicants to hires at each step in the recruitment process.The two findings above tell a lot about the efficiency of the practices of the firm's human resource managers.It is quite safe to say that their ratings were only based on their perceptions and were not based on any empirical evidence because only 25.6 percent and 24.2 percent of them conducted the time-lapse and yield and yield ratio study.These finding expose weakness in the practice of staffing among the companies in Malaysia because without these data, it is very hard for any practitioners to do the human resource planning and staffing effectively and efficiently.However, in terms of the training aspect for the recruiters, majority of the organizations do provide some training on the process of recruitment before they were given a recruitment assignment, do not give a recruitment assignment to their recruiters before they fully understand the knowledge, skills, abilities, and experience required for the vacant jobs and do not give a recruitment assignment to their recruiters before they fully comprehend the values and goals of the organization.These findings reveal quite a good sign of concerned of the human resource managers towards the quality of hiring even though they did not maintain any record on the time-lapse data and yield ratio.